THE PATH TO SPIRITUALITY: A CRITIQUE OF MEREDITH B. MCGUIRE’S VIEW ON SPIRITUALITY AND MATERIALITY - Fatkhuri, Fatkhuri; Truna, Dody S.; Hannah, Neng (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
This article critiques McGuire’s (2008) work on Spirituality and Materiality: Why Bodies Matter? in the book Lived Religion: Faith and Practice in Everyday Life. In her work, McGuire challenges the traditional Western dichotomy between spirituality and materiality, which places the two in a binary opposition. She argues that spiritual experiences are closely connected to the body and physical environment. This article aims to analyze the main strengths of McGuire’s work, particularly its strong empirical foundation through qualitative research methods, such as interviews and observations, which enhance the credibility of her arguments. However, several weaknesses are identified in this study. First, McGuire does not clearly define spirituality, leading to ambiguous interpretations. Second, her generalization that material aspects are always involved in achieving spirituality overlooks the possibility of non-material approaches, such as meditation or introspection. Third, the work neglects psychological factors that influence individual spiritual experiences, such as trauma or motivation. Fourth, the concept of materiality is problematic, as she does not adequately explain how it leads to spiritual experiences. Lastly, McGuire’s in some cases’ use of her personal experiences as a basis for her arguments could introduce bias, as spirituality is highly subjective and varies for each individual. This study employs a qualitative approach to provide an in-depth analysis of McGuire’s work and relevant literature on spirituality and materiality, focusing on how different traditions define and practice spirituality, particularly about pathways that emphasize non-material aspects in achieving spiritual experiences.